EFFECTS OF LATE BLIGHT RESISTANT POTATO CONTAINING RB GENE ON THE SOIL MICROBES, PESTS AND PLANT DISEASES - Riyanti, Eny Ida; Listanto, Edy; Ambarwati, Alberta Dinar (Indonesian Agency for Agricultural Research and Development - MOA, 2014)
Late blight caused by Phytophthora infestans is an important disease on potato. Â Several potato hybrids have been generated by crossing local varieties (Atlantic and Granola) with Katahdin SP951 which contains late blight resistance gene RB. Â Prior to release, these hybrids need to be evaluated for their environ-mental effects on non-target organisms and natural pests and diseases. The objectives of the study were to investigate the effect of LBR potato hybrids on beneficial soil microbes, pests and diseases. The trial was conducted in the confined field trial (CFT) in Lembang, West Java. The parental non-transgenic (NT) clones (Granola, Atlantic and Katahdin) and LBR hybrids (four clones of Atlantic x Katahdin SP951 hybrids; 10 clones of Granola x Katahdin SP951) were planted at a plant spacing of 30 cm x 70 cm. Fungicide applications were used as treat-ments (no spray, five and twenty times sprays). The experi-ment was arranged in a randomized completely block design with three replications. The parameters determined were popula-tions of N2 fixing and P solubilizing bacteria, soil C/N ratio as well as natural pests and diseases. The results showed that the transgenic LBR potato hybrids did not have negative effect on N fixing bacteria. The bacterial populations were around 1010-11 cells g-1 soil before planting, 1012 cells at 1.5 months after planting (MAP) and 108 cells after harvest. For P- solubilizing bacteria, their populations were 1010 cells before planting, 1012 cells at 1.5 MAP and 1011 cells g-1 Â soil after harvest. The soil C/N ratio of the transgenic plot was not statistically different compared to non-transgenic plot, i.e. 12-15 before planting, 10-11 at 1.5 MAP, and 10 after harvest in non-spray plot. Pests and diseases such as Alternaria solani, Liriomyza, potato tubber moth, aphid and mites on the transgenic and non-transgenic plots were statistically not different. The resistance score for A. solani was 7.2 (parental tansgenic) and 7.6 (parental non-transgenic); for Liriomyza it was 2.07 (parental transgenic) and 2.32 insect per plant (parental non-transgenic), the PTM was 0.63 (parental transgenic) and 0.73 insect per plant (parental non-transgenic), aphid and mites were 0.75 (parental transgenic) and 1.68 insects per plant (parental non-transgenic). The study indicated that LBR potato hybrids did not have any negative impacts on non-target organisms.